PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MUSI BANYUASIN - Desi Ulpa Anggraini; Ika Rakhmalina; Ropal Tores (Jurnal Manajemen Kompeten, 2023)
ABSTRACT This study aims to determine the effect of Organizational Citizenship Behavior on Employee Performance at the Office of Public Works and Spatial Planning in Musi Banyuasin Regency. This study used a quantitative method, this research was conducted on employees of the Office of Public Works and Spatial Planning of Musi Banyuasin Regency, the source of the research data was primary data and secondary data with data collection techniques using questionnaires, observation, questionnaires and documentation. The population in this study were employees of the Public Works and Spatial Planning Office of Musi Banyuasin Regency. The sample in this study was 117 respondents using Sugiyono's theory of probability sampling technique, namely a technique that provides equal opportunities for each element (member) of the population to be selected as a sample. The data processing technique for this research used the SPSS version 22 computer. The results of this study indicate that Organizational citizenship behavior (X) influences employee performance (Y). This is based on a correlation value of 0.408 with a significance level of 1.000, which means Organizational citizenship behavior and employee performance have a moderate relationship. In the t test (hypothesis test), the value of tcount > ttable is 4.785 > 1.980 and is corroborated by sig. T is 0.000 <0.05, which means that Organizationalal citizenship behavior influences employee performance improvement. Keywords : Organizational Citizenship Behavior, Employee Performance, Office of Public Works and Spatial Planning of Musi Banyuasin Regency.